Within the Green, We Grow: Nature Schooling, Care, and Neocolonial Entanglements in Bali, Indonesia - Milena Fischer (Humaniora, 2025)
This article examines the proliferation of international nature-based schools in Bali, Indonesia, focusing on how nature schooling communities cultivate visions of ‘good’ lives and sustainable futures while reproducing neocolonial dynamics. Drawing on three months of ethnographic fieldwork conducted in summer 2024, this article investigates why expatriate families are drawn to Bali to educate their children in alternative, holistic, and ‘natural’ environments. The primary site of inquiry is Future Earth School—an international nature school in the southern part of the tourist- and expatriate-favoured island. Theoretically, this article employs a ‘reprolens’—viewing education as a reproductive practice—and draws on feminist ethics of care to analyse how nature schooling embodies both moral aspirations and socio-political contradictions. It shows how romanticised imaginaries of Bali as a natural, caring, and spiritually enriching environment shape educational aspirations and practices while intersecting with transnational mobility, privilege, and uneven power relations. It reveals that international nature schools foster commitments to children, communities, and more-than-human worlds through child-centred, community-oriented, and sustainability-focused pedagogies. At the same time, these schools remain embedded within contexts of environmental degradation, social inequality, and development pressures that they seek to address. Thus, the article argues that nature schooling functions as an exclusive space of care that simultaneously cultivates alternative futures and reproduces neocolonial dynamics under the guise of care and sustainability. In doing so, it demonstrates how nature-based education in Bali serves as a lens to understand the island’s broader sociopolitical dynamics.